2002
DOI: 10.1002/14651858.cd002296
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of NSAID-induced gastroduodenal ulcers

Abstract: Analysis 1.7. Comparison 1: Misoprostol vs placebo -primary e icacy, Outcome 7: Total endoscopic ulcers Chan 2001 removed Prevention of NSAID-induced gastroduodenal ulcers (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
304
2
26

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 346 publications
(356 citation statements)
references
References 89 publications
7
304
2
26
Order By: Relevance
“…An important detail that has been neglected by these authors is the reinfection rate. This study revealed a reinfection of 8,69% over an average follow-up period of three years, similar to the one found by Schutze, et al 23 .…”
Section: Discussionsupporting
confidence: 92%
“…An important detail that has been neglected by these authors is the reinfection rate. This study revealed a reinfection of 8,69% over an average follow-up period of three years, similar to the one found by Schutze, et al 23 .…”
Section: Discussionsupporting
confidence: 92%
“…The advisory committee members voted 16 to 9 against a change in labeling for specific NSAIDs, suggesting that further evidence on the safety of NSAIDs may be warranted 7 . Famotidine, through inhibition of histamine 2 (H2) receptors, prevents NSAID-induced UGI ulceration by reducing gastric acid secretion [13][14][15][16] and has a longer duration of action than other H2-receptor antagonists (H2RAs) 15,17 . Moreover, famotidine may be a practical alternative to proton pump inhibitors (PPIs) in some patients because it is more ideally paired with shorter half-life NSAIDs, such as ibuprofen, from a pharmacokinetic and patient adherence perspective 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from the literature demonstrates that double doses of H2RAs produce significant relative risk (RR) reductions in gastric and duodenal ulcers (RR ¼ 0.44, 95% confidence interval [CI] 0.26-0.74 and RR ¼ 0.26, 95% CI 0.11-0.65, respectively), and are as efficacious as PPIs for the prophylaxis of GI damage from NSAIDs, and are better tolerated than misoprostol 13,22 .…”
Section: Introductionmentioning
confidence: 99%
“…The most prominent members of this group are aspirin (5), ibuprofen (6), naproxen (7), diclofenac (8), and indomethacin (9). Most NSAIDs inhibit the activity of cyclooxygenase-1 and cyclooxygenase-2 and thereby the synthesis of prostaglandins and thromboxanes.…”
Section: Introductionmentioning
confidence: 99%
“…Most NSAIDs inhibit the activity of cyclooxygenase-1 and cyclooxygenase-2 and thereby the synthesis of prostaglandins and thromboxanes. Inhibiting COX-2 leads to the desirable antiinflammatory, analgesic and antipyretic activities whereas the inhibition of COX-1 leads to undesirable side effect like gastrointestinal bleeding 8 , kidney problems 9 , and central nervous system (CNS) effects 10 . The work of Caughey et al 11 and Varas-Lorenzo et al 12 has associated NSAIDs use with increased risk of stroke.…”
Section: Introductionmentioning
confidence: 99%